Financial market development in host and source countries and their effects on bilateral foreign direct investment - Julian Donaubauer; Eric Neumayer; Peter Nunnenkamp (The World Economy, 2019)
We study an underexplored research question, namely whether financial market development in both host and source countries has an effect on bilateral stocks of foreign direct investment (FDI) and, particularly, whether the effect of financial market development in one member of the country pair conditions the effect of financial market development in the other member. We estimate gravity-type models in a global sample of 43 source and 137 host countries over the period 2001–12. We address reverse causality concerns by restricting the sample to observations where reverse causality, if existent, should be less relevant. Our major and robust findings are that bilateral FDI increases with better developed financial markets in both the host and the source country and that for developing host countries, financial market development in source and host countries functions as substitutes for each other.
Keywords: 330; financial market development; foreign direct investment; gravity model